2009
DOI: 10.3354/meps08019
|View full text |Cite
|
Sign up to set email alerts
|

Oligochaetes as a possible entry route for terrigenous organic carbon into estuarine benthic food webs

Abstract: Estuaries receive large quantities of terrestrially derived organic material, yet the current view is that such terrestrial carbon is unimportant for temperate estuarine benthic trophic dynamics beyond microbial processing. This consensus, however, may derive from a lack of consideration in estuarine food web studies of taxa with evolutionary affinities to freshwater systems where these taxa process terrestrial detritus. Here, we used a multiple stable isotope approach (carbon, nitrogen and sulphur) in 3 simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Our study shows that utilization of riverine OM differed among feeding groups of benthic primary consumers in the Vistula River prodelta. Common species of obligatory and facultative deposit feeders i.e., Oligochaeta (Attrill et al, 2009), P. elegans (Brey, 1991), Marenzelleria spp. (Dauer, 1997) and H. diversicolor (Fauchald and Jumars, 1979) showed a higher contribution of rPOM in their diet in comparison to obligatory suspension feeders (C. glaucum, M. arenaria).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that utilization of riverine OM differed among feeding groups of benthic primary consumers in the Vistula River prodelta. Common species of obligatory and facultative deposit feeders i.e., Oligochaeta (Attrill et al, 2009), P. elegans (Brey, 1991), Marenzelleria spp. (Dauer, 1997) and H. diversicolor (Fauchald and Jumars, 1979) showed a higher contribution of rPOM in their diet in comparison to obligatory suspension feeders (C. glaucum, M. arenaria).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings also showed that deposit feeders may to some degree rely on terrigenous OM (Darnaude et al, 2004;McGovern et al, 2020) that is one of the main components of OM transported by rivers. Attrill et al (2009) suggested that higher reliance of Oligochaeta on terrigenous matter is probably the result of their evolutionary association to freshwater ecosystems that to a large extent are subsidized by terrigenous detritus. Since most deposit feeders feed rather non-selectively on sedimentary detritus (Levinton, 1989), it is likely that terrigenous OM contribution in the diet of other deposit-feeding species is higher than for obligatory suspension feeders.…”
Section: The Role Of Feeding Modes In Rpom Consumptionmentioning
confidence: 99%
“…The carbon and nitrogen isotopic compositions of suspended particulate matter (particulate organic matter, POM), sediments (sediment organic matter, SOM) and benthic organisms were expressed with the standard δ unit notation, given in parts per thousand (‰), according to the following equation: where X is the stable isotope ratio of δ 13 C or δ 15 N, R is the ratio of 13 C/ 12 C for carbon or 15 N/ 14 N for nitrogen for sample and for standard reference material (Pee Dee Belemnite (PDB) for δ 13 C and air for δ 15 N) (Khan et al 2015 ). Data pertaining to the δ 13 C and δ 15 N values in selected ecosystem components used in this study were taken from a simultaneous research project being conducted by the authors (Jędruch et al 2017 ), as well as from literature (Hansson et al 1997 ; Riera et al 1999 ; Attrill et al 2009 ; Nordstöm et al 2009 ; Sokołowski 2009 ; Kolb et al 2010 ; Riera 2010 ; Olsen et al 2011 ; Prado et al 2013 ; Karlson et al 2015 ; Jankowska et al 2016 ; Jankowska 2017 ; Jankowska et al 2018 ). The majority of literature data were obtained from the Puck Lagoon and at similar time as this study (Table SI ).…”
Section: Methodsmentioning
confidence: 99%
“…In one study, estuarine oligochaetes had stable isotopic signals similar to soil organic carbon, while estuarine amphipods and polychaetes were supported by marine algae (Attrill et al, 2009). These differences were most likely due to differential digestion rather than selective ingestion, as different sources of organic matter are mixed together in seston and sediment.…”
Section: Terrestrial Organic Mattermentioning
confidence: 99%